Student Perceptions in Measuring Teaching Behavior Across Six Countries: A Multi-Group Confirmatory Factor Analysis Approach to Measurement Invariance - André, Stéfanie; Maulana, Ridwan; Helms-Lorenz, Michelle; Telli, Sibel; Chun, Seyeoung; Fernández-García, Carmen-María; de Jager, Thelma; Irnidayanti, Yulia; Inda-Caro, Mercedes; Lee, Okhwa; Safrina, Rien; Coetzee, Thys; et al. (Frontiers in Psychology, 2020)
The purpose of this study is to examine measurement invariance of scoring of teaching behaviour, as perceived by students, across six cultural contexts (The Netherlands, Spain, Turkey, South Africa, South Korea, and Indonesia). It also aims to compare perceived teaching behaviour across the six countries based on a uniform student measure. Results from multi-group confirmatory factor analyses (MGCFA) showed perceived teaching behaviour in the six countries to be adequately invariant. Perceived teaching behaviour was the highest in South Korea and the lowest in Indonesia. The findings provide new insights into the relevance and differences of teaching behaviour across cultural contexts.